On a Class of Generalized Hydrodynamic Type Systems of Equations - Fedorov, V.E.; Davydov, P.N. (Journal of Applied Nonlinear Dynamics, 2026)
By means of the degenerate semigroups theory methods the local existence of a unique solution is proved for initial-boundary value problems to a class of partial differential equations systems of generalized hydrodynamics type. General results are illustrated by examples of a system with the nonlinear viscosity and a weighted system.